Pengelolaan Kurikulum dan Pembelajaran Berbasis Pesantren di SMP - Prabowo, Yunanto Ari (Universitas Muhammadiyah Surakarta, 2016)
This study was to describe the (1) foundation and implementation of curriculum- based learning Pesantren (2) implementation based learning curriculum and Pesantren (3) factors that support and hinder the implementation of the curriculum and learning-based schools. The method in this study used a descriptive approach kualitatif.Teknik data collection are observation, interview, and documentation. To test the validity of the data using a triangulation method, Results of this study were (1) SMP Muhammadiyah Darul Ihsan using curriculum KTSP 2006 is based on official curriculum and uniquely pesantren (2) Study carried out other than in accordance formal school hours learning is also conducted during the students stay in dormitories. (3) The factors supporting that policy right schools, the teachers are professional and complete infrastructure. While inhibiting factors include: conditions of students or students who are less responsible in terms of learning so that they seem still like to play around and learn less than the maximum.